Keindahan Visual Dalam Konten Video Ria SW di YouTube Bagi Pelanggan - Agustini,; Hermanto, Salsabilla; Suryatna, Undang (JURNAL KOMUNIKATIO, 2025)
Visual beauty in video content is one of the main factors that determine the attractiveness and success of a work on digital platforms, including YouTube. This study focuses on video content produced by Ria SW, a creator known for his culinary and travel videos, and how subscribers in Bogor interpret the visual beauty displayed. The purpose of the study was to explore the audience's perception of the visual elements present in the video Ria SW and join in building a pleasant viewing experience. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, direct observation on video content, as well as the study of relevant literature. The results showed that the visual beauty presented through balanced image composition, aesthetic color selection, appropriate lighting, and presentation of food that uploads tastes, became the most prominent aspects in building the attractiveness of the content. The Visual not only adds to the comfort and satisfaction of watching, but also serves to strengthen the message of information to be conveyed Ria SW. In addition, customers in Bogor city feel an emotional closeness with Ria SW through warm, natural, and authentic visual nuances. This shows that the visual aspect does not just act as a complement, but becomes an important part in building emotional interactions between creators and audiences. Overall, this study confirms that visual beauty in YouTube video content has a significant contribution in improving the viewing experience, strengthening the appeal of information, and creating an immersive emotional atmosphere for customers.